A Study of Risk Disclosures in the Annual Reports of UK and Malaysian Companies - Yap, Hui Ying (2011)
The research paper compares the nature and extent of risk disclosure practices between United Kingdom (UK) and Malaysian listed companies for the financial year 2010. In addition, the relationships between the level of risk disclosures and firm's characteristics such as size, industry classification, foreign listing status, country of domicile, level of risk and profitability are examined using multiple regression. Following a disclosure index study, both the UK and Malaysian companies are found to disclose more on financial risk information such as foreign exchange risk, interest rate risk, credit risk and liquidity risk. The results show that most of the UK and Malaysian companies quantify the financial risk exposures compared to non-financial risk exposures. In addition, companies are found to disclose moderate amount of forward-looking risk information. Most of the companies have a specific section for reporting risk and risk management information. However, only a small proportion of companies have referred to risk appetite, the implementation of Enterprise Risk Management (ERM) and the appointment of risk committee in the annual reports. In overall, UK companies disclose more risk information than Malaysian companies in almost every aspect of risk disclosures mentioned above, except for the disclosure on implementation of ERM and appointment of risk committee. The results from multiple regression show that size, foreign listing status and country of domicile are statistically significant in explaining the level of risk disclosure, measured in total disclosure index (TDI).